FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN DISTRESS EMOSIONAL PADA CAREGIVER PEREMPUAN DENGAN ANGGOTA KELUARGA YANG MENGALAMI GANGGUAN JIWA - ira Erwina; reni prima gusty; Monalisa - (Ners Jurnal Keperawatan, 2016)
Abstract                                                                                                                 Caring for mental patients can be done by families and health professionals. The family is the closest to patients with mental disorders, referred as caregiver. Caregiver always give support for patient care. Caring for patients with mental disorders will make caregivers vulnerable to emotional problems such as anxiety, depression and worries. The purpose of this study was to determine the emotional distress experienced by female caregiver and the characteristics and its relationship with mental patients. Design of this research is analytic survey with purposive sampling technique. The total sample of 86 respondents, data were collected using questionnaires. The results of the data obtained and tested using correlation analysis. The result is women caregivers for experiencing emotional distress is 7.73 (77.3%), and there is a relationship between the family situation (caregiver relationship and supervision) to emotional distress, and there is no relationship between the characteristics of caregivers and the characteristics of mental disorder patients with emotional distress. Advised the caregiver to seek information and to improve the ability to solve problems. Keywords      : caregiver, women, emotional distress, mental disorders Abstrak Merawat pasien gangguan jiwa bisa dilakukan oleh keluarga dan tenaga kesehatan. Keluarga adalah orang yang terdekat dengan pasien dengan gangguan jiwa, yang disebut dengan istilah caregiver. Caregiver selalu memberikan support dan dukungan selama merawat pasien. Merawat pasien dengan gangguan jiwa akan membuat caregiver rentan terhadap masalah emosional seperti cemas, depresi dan kekhawatiran. Tujuan penelitian ini adalah untuk mengetahui distress emosional yang dialami caregiver perempuan dan hubungannya dengan karakteristik caregiver dan pasien gangguan jiwa. Desain penelitian ini adalah survey analitik dengan teknik purposive sampling. Jumlah sampel sebanyak 86 orang, data dikumpulkan menggunakan kuisioner. Hasil data diperoleh dan diuji menggunakan analisis korelasi. Hasilnya adalah caregiver perempuan mengalami distress emosional sebesar 7,73 (77,3%), dan terdapat hubungan antara situasi keluarga (hubungan caregiver dan pengawasan) terhadap distress emosional, dan tidak terdapat hubungan antara karakteristik responden dan karakteristik pasien gangguan jiwa dengan distress emosional. Disarankan pada caregiver untuk mencari informasi dan meningkatkan kemampuan untuk mengatasi masalah. Kata kunci   : caregiver, perempuan, distress emosional, gangguan jiwa